Application Barriers and the Socioeconomic Gap in Child Care Enrollment - Henning Hermes; Philipp Lergetporer; Frauke Peter; Simon Wiederhold (Institute of Labor Economics (IZA), 2024)
Why are children with lower socioeconomic status (SES) substantially less likely to be enrolled in child care? We study whether barriers in the application process work against lower-SES children — the group known to benefit strongest from child care enrollment. In an RCT in Germany with highly subsidized child care (N = 607), we offer treated families information and personal assistance for applications. We find substantial, equity-enhancing effects of the treatment, closing half of the large SES gap in child care enrollment. Increased enrollment for lower-SES families is likely driven by altered application knowledge and behavior. We discuss scalability of our intervention and derive policy implications for the design of universal child care programs.
Keywords: I21; J13; J18; J24; C93; 330; educational inequality; information; application barriers; early childhood; child care; randomized controlled trial